Perceptions of residents of hosting the “Guimarães 2012 European Capital of Culture”: An ex-ante approach - Remoaldo, Paula (2014)
The European Capital of Culture is an annual mega-event, which can provide a good forum though which to challenge and engage local citizens, thus generating feelings of common citizenship. In addition, it presents an ideal opportunity to promote the restructuring of the hosting urban space. However, the success of both the organization and the city that hosts the cultural event depends on the residents’ commitment towards it, the consistency of the tourism attractions and activities supplied, and the capacity of anticipating and monitoring the evolution of tourists’ preferences. The present study aims to assess the intention to participate and the impacts perceived by residents of Guimarães from hosting one of the 2012 European Capitals of Culture (2012 ECOC) in the ex-ante period (2011). Through a convenience sample of 471 usable surveys applied to the local population, conducted between October and December 2011, we tried to identify some of these potential impacts. According to the results received, 40% of residents had a low or very low knowledge of the cultural program, although only 11% demonstrated no intention of attending any activity during the event. The comparison of the mean scores of the expected 2012 ECOC impacts by gender reveals that the most valued and least valued factors are common to female and male respondents. With regard to the differences between those that intended to attend the event and the ones that did not, expected participants rated positive and negative impact factors more than did the ones that did not intend to attend.